The Norwegian National Insurance Scheme as the main element of the Norwegian “welfare state” - Nowiak, Wojciech (Folia Scandinavica Posnaniensia, 2007)
The National Insurance Scheme is the main element of the Norwegian ’’welfare state”. The Scheme secures people’s finance when they are sick, disabled, unemployed or old, or when they have no one to support them and are unable to support themselves. The National Insurance Scheme is the most fundamental cornerstone of the structure represented by the ’’welfare state”. The Scheme consists of long-term benefits; pensions and transitional allowances; short-term benefits; daily allowances for the sick, and daily cash benefits for the unemployed and benefits in kind; and expenditure for health care and rehabilitation.